Analysis of retinal sublayers in patients with systemic COVID-19 illness with varying degrees of severity - Mohammad Reza Talebnejad; Mohammad Reza Badie; Hossein Shahriari; M. Hossein Nowroozzadeh (Scientific Reports)
Abstract COVID-19 infection has been linked to ocular involvement, particularly retinal microvascular changes. Additionally, prolonged hypoxemia may affect retinal sublayers located within the retinal watershed zone. The aim of this study was to evaluate retinal and optic nerve OCT parameters in patients with COVID-19 illness of varying severity and compare them with controls. In this prospective case-control study, a total of 78 consecutive patients who had recently recovered from SARS-CoV-2 infection (29 outpatients, 32 ward-admitted patients, and 17 ICU-admitted patients) were included, along with 85 controls. All participants had no ocular disease or symptoms. Spectralis SD-OCT scans of the macula and optic nerve were obtained from all participants 6 weeks after initial diagnosis. The central subfield thickness of the macula (CSFT), peripapillary retinal nerve fiber layer thickness (pRNFL), and retinal sublayers’ volumes in the total 6-mm ETDRS zone were recorded and analyzed using the ANCOVA test, adjusting for age. The mean CSFT in controls was 271 μm, while in the outpatient, ward-admitted, and ICU-admitted groups, it was 251, 260, and 253 μm, respectively (P = 0.093). No differences were observed in pRNFL between the groups (P> 0.1). However, the outer plexiform layer (OPL) was the only retinal sublayer that demonstrated a significant difference in 6-mm volume across the groups, with volumes of 0.832 μm3 in controls, 0.822 μm³ in the outpatients, 0.814 μm³ in ward-admitted patients, and 0.785 μm³ in ICU-admitted cases (P = 0.006). Our findings suggest that patients with severe COVID-19 illness, especially those requiring respiratory support, may develop ischemia and atrophy of the OPL. This indicates that the OPL might be the most vulnerable retinal sublayer to systemic hypoxemia, a hypothesis that requires confirmation through future studies.